Analisis Yuridis Kegiatan Spionase Melalui Fasilitas Diplomatik dan Konsular - Aryo Dewanto, Wisnu; Lisanawati, Go (Perspektif Hukum, 2023)
This paper discusses espionage activities conducted by states to obtain and collect confidential and important information through diplomatic and consular facilities. Diplomatic and consular facilities are considered an extension of the sending state's territory in the receiving state and are protected by international law that serves to facilitate international relations with states. This paper will examine important issues related to the extent to which these espionage activities violate international law and the legal mechanisms to address them. Furthermore, it mentioned cases in which states have been accused of espionage through their diplomatic and consular facilities, and the impact this has had on interstate relations, and provides a better insight into the complexity of the espionage issue, including maintaining integrity and principles in diplomacy.